Nursing care related to fall prevention among hospitalized elderly people: an integrative review - Adnairdes Cabral de Sena; Angela Maria Alvarez; Simony Fabíola Lopes Nunes; Nadia Pinheiro da Costa (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to identify scientific productions on nursing care related to fall risk prevention among hospitalized elderly people. Methods: an integrative literature review from 2015 to 2019 in the PubMed/MEDLINE, Scopus, Web of Science, LILACS, BDENF, SciELO and CINAHL databases, in Portuguese, English and Spanish. The keywords were elderly, hospitalization, accidents due to falls, nursing care. Results: thirty-three publications were analyzed. The synthesis of the studies resulted in the categories: Clinical nursing assessments to prevent falls among hospitalized elderly people; Fall risk factors for elderly people; Fall risk prevention strategies for elderly people. Final considerations: it was found that the scientific knowledge produced on nursing care related to fall risk prevention for hospitalized elderly people evidences the clinical assessment, risk factors and strategies such as nursing care, contributing to foster self-care behavior and promotion security for elderly people.